2002
DOI: 10.1038/sj.mp.4001043
|View full text |Cite
|
Sign up to set email alerts
|

Opposite modifications in circulating leptin and soluble leptin receptor across the eating disorder spectrum

Abstract: Leptin is thought to modulate feeding behaviour, body weight and energy metabolism by acting through specific cellular receptors. Derangements of leptin production have been repeatedly reported in patients with anorexia nervosa (AN) or bulimia nervosa (BN), but no information has been provided on the functional status of leptin receptors in these disorders. Therefore, we measured plasma levels of leptin and its soluble receptor (Ob-Re) in a total of 130 women, including 22 patients with AN, 45 patients with BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 30 publications
4
40
1
4
Order By: Relevance
“…Data from the study by Monteleone et al are consistent with our findings. These authors observed in AN patients low concentrations of leptin and increased values of leptin receptor [19]. Our results also corroborate with those of the group of Misra, who reported a markedly reduced plasma leptin concentration coexisting with enhanced concentration of sOB-R and decreased FLI in AN participants in comparison with healthy adolescents [17].…”
Section: Prace Oryginalnesupporting
confidence: 92%
See 1 more Smart Citation
“…Data from the study by Monteleone et al are consistent with our findings. These authors observed in AN patients low concentrations of leptin and increased values of leptin receptor [19]. Our results also corroborate with those of the group of Misra, who reported a markedly reduced plasma leptin concentration coexisting with enhanced concentration of sOB-R and decreased FLI in AN participants in comparison with healthy adolescents [17].…”
Section: Prace Oryginalnesupporting
confidence: 92%
“…A correlation between decreased BMI and low levels of leptin were also described in accessible literature [15][16][17][18][19].…”
Section: Prace Oryginalnementioning
confidence: 88%
“…This is probably because B vitamins are known to increase appetite [15], possibly leading to weight gain and/or obesity and hence, indirectly increasing leptin levels. The circulating levels of leptin have been shown to be influenced by amount of body fat, with higher levels in obese than in lean individuals [29]. However, conflicting findings are reported for leptin concentration differences with similar fat mass [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize, therefore, that the regulation of leptin and sOB-R may be independent from one another at manifestation of T1DM and during its treatment. This must not be the case in non-diabetic subjects, where leptin or fat mass differences may influence sOB-R serum levels (27,28). The biological impact of increased sOB-R levels in newly diagnosed diabetes is presently unclear.…”
Section: Discussionmentioning
confidence: 99%